Agroforestry for soil conservation and other natural resources (Revista Sistemas de Producción Agroecológicos, 2013)
A definition of agroforestry that covers various aspects is interdisciplinary science with tradition, innovation production and conservation of nature where there are forms of management and use of systems and development of traditional and novel, strengthening cultural identity, total ecological interactions complementarity system, landscape diversification, proper use of natural resources, human labor privilege, using technologies with low environmental impact and which are social, environmental and economic welfare, equity and justice. The fact decrease hectares of forest in South America, has produced loss of biodiversity, degradation of natural resources (water, air and soil), and displacement of indigenous tribes, which has caused a decline in agricultural and animal productivity, and last but not least, a high poverty rate, rural populations who are dedicated to these activities. This is due, custom to have the South American countries, to implement models with a high dependence on agrochemicals, where production systems are based on monocultures, with imported technology packages, implementation of agricultural machinery unsafe the tropics, which contributed to the worsening environmental crisis which we are now passing. A series of arguments have been raised, oriented towards sustainability considering strategies for the conservation of natural resources, and energy in its cyclicality, in which the "agroforestry", play an important role due to the large variety of tree species found in the tropics of South America, seeking to friendly systems environment and so provide an optimal quality of life for farmers and their environment, increasing plant and animal productivity and improving landscapes.
Keywords: sustainability; agroforestry system